Sexual dimorphism and regional variations in size and reproduction of Cuttlefish, Sepia officinalis L. 1758 (Sepiida, Coleoidea) in Libyan waters - Hisham Mohammed Ghmati; Hend Assiad Ensair; Akraam Faraj Kara; Mohamed Milad Elhejaji; Abdelkader Salim Abid; Hosnia Ahmed Al-Maghbon; Nazik Saed Altrabulsi; Walid Khalifa Saadawi (African Journal of Advanced Pure and Applied Sciences, 2024)
This study presents a comprehensive investigation of various population dynamics and reproductive parameters in Sepia officinalis in the coastal waters of Libya, Utilized a dataset of 1171 individuals. This study focuses on potential differences in sex-based and regional variations, between Tripoli and Benghazi subpopulations. The result confirmed sexual dimorphism, in smaller males. The sex ratio is nearly balanced. Most individuals exhibit hypo-allometric growth, their body weight increases at a slower rate than their mantel length. The spawning season for S. officinalis in Libyan waters spans from March to September, reaching its peak during the warmer months of July and August. Females displayed a continuous cycle of ovarian development, with peak ripeness observed throughout the year. Males exhibited a more seasonal pattern, with ripe testes dominating during the warmer months of May to September. The estimated size at first maturity (L50) differed slightly between sexes; females matured earlier and at a slightly smaller 8.42 cm compared to males overall. The study revealed regional variations in size at maturity; The pattern in Tripoli subpopulation deviated from this trend, females matured earlier, reaching a size of 9.06 cm compared to males, who matured at 10.12 cm. Conversely, Benghazi females take their time to reach maturity at a smaller size of 8.32 cm, while Benghazi males matured earlier and were smaller at 6.78 cm.